Benefits and risks of upright positions during the second stage of labour: An overview of systematic reviews. (February 2021) - Zang, Yu; Lu, Hong; Zhang, Huixin; Huang, Jing; Zhao, Yang; Ren, Lihua
Abstract: Background: Upright positions during the second stage of labour are assumed to have many physiological advantages that may facilitate normal birth. Clarifying the underlying benefits and risks of upright positions plays an important role in the implementation of upright positions. The benefits and risks of upright positions during the second stage of labour have been explored in several systematic reviews, but the results are divergent. Objective: To summarize the evidence on the underlying benefits and risks of upright positions during the second stage of labour by searching available systematic reviews to explore the best evidence for clinical practice and decision making. Design: Overview of systematic reviews. Data sources: We systematically searched five English databases and four Chinese databases from inception to 15th March 2020 for any published and ongoing systematic reviews. Review methods: Two reviewers independently evaluated the methodological and the reporting quality of the included systematic reviews using the AMSTAR 2 tool and the PRISMA checklist. A descriptive synthesis was used by reporting the results of the highest quality reviews. Results: Seven systematic reviews met the eligibility criteria, of which two Cochrane reviews had the highest methodological and reporting quality. In women without epidural analgesia, upright positions significantly reduced the rate of instrumental vaginal birth ( moderate-quality evidence ), shortened the second stage of labour ( very low-quality evidence ), reduced the rate of episiotomy ( very low-quality evidence ) and abnormal foetal heart rate patterns requiring intervention ( very low-quality evidence ), but significantly increased the risk of blood loss greater than 500 ml ( moderate-quality evidence ) and second-degree perineal trauma ( low-quality evidence ). However, no definite benefits or risks of upright positions were found in women with epidural analgesia based on the current evidence. Conclusions: This overview demonstrates that upright positions have both benefits and risks but the quality of the current evidence is relatively low. It is necessary for the researchers to conduct robust studies to provide stronger evidence. In addition, upright positions are recommended to be used depending on women's preferences and labour progress, but should also be carefully monitored especially in women with epidural analgesia. Registration number: CRD42020175820